2008
DOI: 10.1124/jpet.107.130609
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Sepsis-Induced Acquired Protein C Deficiency Reverses Angiotensin-Converting Enzyme-2 Inhibition and Decreases Pulmonary Inflammatory Response

Abstract: The protein C (PC) pathway plays an important role in vascular and immune function, and acquired deficiency during sepsis is associated with increased mortality in both animal models and in clinical studies. However, the association of acquired PC deficiency with the pathophysiology of lung injury is unclear. We hypothesized that low PC induced by sepsis would associate with increased pulmonary injury and that replacement with activated protein C (APC) would reverse the activation of pathways associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
(57 reference statements)
2
13
0
Order By: Relevance
“…OA may also promote ALI by increasing the ratio between angiotensin-converting enzymes I and II [ 47 ], upregulating inducible nitric-oxide synthase (iNOS), and inhibiting alveolar epithelial Na,K-ATPase activity [ 48 ]. In rats subjected to cecal ligation and puncture, the investigators found that depletion of protein C was associated with lung injury, upregulation of iNOS, and angiotensin-converting enzyme I/II ratio, all changes that were antagonized by administration of APC [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…OA may also promote ALI by increasing the ratio between angiotensin-converting enzymes I and II [ 47 ], upregulating inducible nitric-oxide synthase (iNOS), and inhibiting alveolar epithelial Na,K-ATPase activity [ 48 ]. In rats subjected to cecal ligation and puncture, the investigators found that depletion of protein C was associated with lung injury, upregulation of iNOS, and angiotensin-converting enzyme I/II ratio, all changes that were antagonized by administration of APC [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACE2 is abundantly expressed in Type II alveolar cells and also in the small intestine but, importantly, ACE2 is also present on vascular endothelia and smooth muscle cells in most organs of the body [ 23 , 24 ]. The vascular endothelial damage induced by the inflammatory response leads to an upregulation of tissue factor expression, downregulation of the protein C system, and activation of the complement system [ 25 , 26 , 27 ]. Injured endothelial cells release their constituents, such as von Willebrand factor (VWF) multimers.…”
Section: Covid-19-associated Coagulopathymentioning
confidence: 99%
“…Arterial oxygenation only was improved in a rat model of endotoxin‐induced sepsis without effect on pulmonary protein leakage (Dubniks and Grande, 2008). In a polymicrobial sepsis model of caecal ligation and puncture (Richardson et al ., 2008), there was a clear reduction in plasma protein C levels correlated with an increase in macrophage inflammatory protein chemokines and increased PAI‐1 levels. Elevated markers of pulmonary inflammation, increased inducible nitric oxide synthase expression and lower ACE2 levels in pulmonary tissue were also associated with lower endogenous protein C levels.…”
Section: Apc and Acute Lung Injurymentioning
confidence: 99%